2000
DOI: 10.1385/abab:84-86:1-9:617
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lignocellulose-Derived Aromatic Compounds on Oxygen-Limited Growth and Ethanolic Fermentation by Saccharomyces cerevisiae

Abstract: Phenolic compounds released and generated during hydrolysis inhibit fermentation of lignocellulose hydrolysates to ethanol by Saccharomyces cerevisiae. A wide variety of aromatic compounds form from lignin, which is partially degraded during acid hydrolysis of the lignocellulosic raw material. Aromatic compounds may also form as a result of sugar degradation and are present in wood as extractives. The influence of hydroxy-methoxy-benzaldehydes, diphenols/quinones, and phenylpropane derivatives on S. cerevisiae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0
26

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(161 citation statements)
references
References 11 publications
8
127
0
26
Order By: Relevance
“…However, this portion can be burned for efficient heating and electrical production and, in the longer term, specialty chemical production (92). The negative impacts of lignin on lignocellulose-based fermentative processes are (i) inhibition of cellulases (50) and (ii) formation during lignocellulose pretreatment of phenolic degradation products which inhibit microbial growth (11,192).…”
Section: Bioethanol Productionmentioning
confidence: 99%
“…However, this portion can be burned for efficient heating and electrical production and, in the longer term, specialty chemical production (92). The negative impacts of lignin on lignocellulose-based fermentative processes are (i) inhibition of cellulases (50) and (ii) formation during lignocellulose pretreatment of phenolic degradation products which inhibit microbial growth (11,192).…”
Section: Bioethanol Productionmentioning
confidence: 99%
“…After this step, the lignocellulose materials become dissolvable in the liquid media that consists of formic, acetic and levulinic acids, as well as phenolic and furans compounds that formed during pretreatment step [215]. Since all of the released chemical compounds had a negative impact on the growth of yeast, bioethanol production and fermentation processes at all [216], alot of endeavors have been exerted to obviate the production of these harmful chemical compounds [4]. An alternative way for overcoming this obstacle is to minimize their concentrations by different application method of detoxification [215], but more procedures have a negative influence on the balance of energy and increase the cost of product which makes it unavailable for application in all conditions [3].…”
Section: Factors Prohibiting the Bioethanol Production From Lignocellmentioning
confidence: 99%
“…Some researches indicated that these compounds partition into cells membranes cause loss of integrity (Palmqvist & Hann-Hägerdal, 2000). It was established that low molecular weight phenolic compounds are more inhibitory than those with high molecular weight (Klinke et al, 2004) and furthermore, the substituent position influenced the compounds toxicity (Larsson et al, 2000). Among the phenolic compounds, vanillin was shown to be a strong inhibitor of growth and ethanol production in P.stipitis, C. shehatae and S.cerevisiae at the concentration of 1 g/L (Delgenes et al, 1996).…”
Section: Inhibitory Compounds Derived From Biomass Pretreatment: Effementioning
confidence: 99%